Relevance and market analysis for decision making in Higher Education institutions: Oﬀer of Master’s degrees in Administrative Sciences in the Colombian Caribbean region - Vassallo-Díaz, Leonardo; Cárdenas-Herrera, Stephanía (EFIM Ediciones, 2020)
The present scientific article gathers the results of the study on the relevance of the supply of new master’s programs in Business Administration in the Caribbean Region and the existing demand through a cross-sectional study implementing a information, 396 participants distributed in the 7 departments of the Caribbean Region. The validation of the existence of an existing demand and the relevance of offering new master’s programs is developed on the basis of concepts of relevance and demand. The results demonstrate the relevance of the offer of new masters programs in the area of Administration for the Caribbean Region.